Real world instructional design : an lterative approach to designing learning experiences - Cennamo, Katherine; Kalk, Debby (New York : Routledge, Taylor & Francis Group, 2019)
An ideal textbook for instructional designers in training, Real World Instructional Design emphasizes the collaborative, iterative nature of instructional design.
Preface. To the Instructor. About the Authors. 1. Introduction to Instructional Design 2. Learner Needs and Characteristics 3. Outcomes and Assessments 4. Activities: Planning Learning Events 5. Activities: Developing Instructional Strategy 6. Evaluation 7. Collaboration and Communication 8. Define Phase 9. Design Phase 10. Demonstrate Phase 11. Develop and Deliver Phases 12. The Professional Designer
Includes bibliographical references and index.
Keywords: Design pédagogique.; Instructional systems Design